Zoneamento de risco climático do cultivo da nogueira pecã (Carya illinoinensis) para o Rio Grande Do Sul - Rovani, Franciele Francisca Marmentini (2016)
This research has objective to elaborate the Climate Risk Zoning of pecan (Carya illinoinensis) in Rio Grande do Sul State. The theoretical review was obtained by reading studies about Climatology, Zonings, contributions of Geotecnologies and the pecan cultivation. The methodology consisted of the collect of climate data in 23 weather stations of INMET distributed in the state territory, pecan production data and tree phenological phases t. The geographic database was elaborated in ArcGIS software 10.2.2. For climate risk zoning were defined the temperature above 35°C, excess rainfall, lack of chilling, drought and excessive relative humidity in different phenological phases. Each climate risk was classified in very low, low, medium, high and very high, and after your integration the zoning was obtained. Spatial interpolation kriging and multiple linear regression analysis were used for seasonal, annual climatic variable and climatic risk spatialization. The significant increase in planted area with pecan during the last years indicated that the pecan cultivation is expanding in Rio Grande do Sul State. The dynamics of climate variables in the state territory indicate that pecan climatic requirements is attended. . This is due to all risk index showed occurrence mainly in very low and low classes. The drought risk index in the fruits formation piorid showed the lowest occurrence (3.1%). However, excess rainfall risk index could affected in four tree phenological phases of the cultivation: foliar expansion, flowering, fruits formation and harvest. The temperatures higher than 35°C is more evident in the phase that the fruit is growingthan at flowering. For chilling lack was observed the five risk classes, with predominance of high and very high risk especially in the Valley of Uruguay River. Coastal plain had medium or high risks for moisture excess. The integrated Climate Risk Zoning presented two risk classes in different climatic regions. The very low climatic risk class is 41.8% of the gaucho territory and includes the areas in which predominated very low risk index or absence of risk for the difference variables. The low climatic risck class was divided into two classes: low - A and low - B. Climatic low risk A represents 51.6% of the territory and includes areas at drought risk (south of the state territory) and low to medium risk of lack of chilling. Climatic low risk - B represents 6.6% the study area, was distinguished from the previous risk in that the present predominance of lack of chilling. This indicated that pecan cultivation has great potential in Rio Grande do Sul state, but for to obtain a good production is necessary observad the climatic restrictions in each area that pecan is growthing.